2009
DOI: 10.1002/mabi.200800223
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Double‐Network Hydrogel Induces Spontaneous Articular Cartilage Regeneration in vivo in a Large Osteochondral Defect

Abstract: We have developed a novel method to induce spontaneous hyaline cartilage regeneration in vivo for a large osteochondral defect by implanting a plug made from a double-network hydrogel composed of poly(2-acrylamido-2-methylpropanesulfonic acid) and poly(N,N'-dimethylacrylamide) at the bottom of the defect, leaving the cavity vacant. In cells regenerated in the treated defect, type-2 collagen, Aggrican, and SOX9 mRNAs were highly expressed and the regenerated matrix was rich in proteoglycan and type-2 collagen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
157
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 38 publications
4
157
0
3
Order By: Relevance
“…Despite their high water content (90 wt%), DN gels synthesized with such an optimized composition exhibit high elastic modulus (0.3-1.0 MPa), and high compressive fracture strengths, similar to natural cartilages (20 MPa) [11,13]. The DN principle to synthesize the tough hydrogels was further applied to various polymer combinations, and tough DN gels with good biocompatibility [14][15][16], low sliding friction [17], and excellent wear resistance [18] have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high water content (90 wt%), DN gels synthesized with such an optimized composition exhibit high elastic modulus (0.3-1.0 MPa), and high compressive fracture strengths, similar to natural cartilages (20 MPa) [11,13]. The DN principle to synthesize the tough hydrogels was further applied to various polymer combinations, and tough DN gels with good biocompatibility [14][15][16], low sliding friction [17], and excellent wear resistance [18] have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The overall charge carried on hydrogels can heavily influence cell adhesion and behavior. Positively charged surfaces are known to increase cell attachment and proliferation; as demonstrated by Schneider et al [23] Negatively charged hydrogels have also been shown to increase proliferation of endothelial cells [30] and improve cartilage regeneration in vivo, [31] although Liu et al [32] observed decreased fibroblast proliferation on negatively charged hydrogels. These differences in findings about which charge cells favor lead us to speculate that certain cells prefer a specific charge, be it positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…NaSS and NaAMPS have good biocompatibility, which means nontoxic due to their sodium-form of chemical structure. Indeed, DN gels are used as test beds for cell culture [6]. DMAAm is convenient to be used due to its high reactivity in gelation and good ductility.…”
Section: Introductionmentioning
confidence: 99%